Cationic octahedral molybdenum cluster complexes functionalized with mitochondria-targeting ligands: photodynamic anticancer and antibacterial activities. (18th January 2019) - Kirakci, Kaplan; Zelenka, Jaroslav; Rumlová, Michaela; Cvačka, Josef; Ruml, Tomáš; Lang, Kamil
Abstract : Octahedral molybdenum cluster complexes bearing mitochondria-targeting terminal functions are attractive candidates for photodynamic applications and luminescent probes. Abstract : Octahedral molybdenum cluster complexes have recently come forth as pertinent singlet oxygen photosensitizers towards biological applications. Still, their phototoxic efficiency in the absence of nanocarriers remains limited due to their poor cellular uptake. Here, two cationic octahedral molybdenum cluster complexes, bearing carboxylate ligands with triphenylphosphonium (1 ) or N -methyl pyridinium (2 ) mitochondria-targeting terminal functions, have been designed and synthesized. Their photophysical properties in water and in vitro biological activity were investigated in the context of blue-light photodynamic therapy of cancer and photoinactivation of bacteria. Upon blue light irradiation, complex1 displays red luminescence with a quantum yield of 0.24 in water, whereas complex2 is much less emissive ( Φ L < 0.01). Nevertheless, both complexes efficiently produce singlet oxygen, O2 ( 1 Δg ). Complex1 is rapidly internalized into HeLa cells and accumulated in mitochondria, followed by relocation to lysosomes and clearance at longer times. In contrast, the more hydrophilic2 is not internalized into HeLa cells, highlighting the effect of the apical ligands on the uptake properties. The treatment with1 results in an intensive phototoxic effect under 460 nm irradiation (IC50 = 0.10 ± 0.02 μM), which exceeds by far those previously reported for octahedral cluster-based molecular photosensitizers. The ratio between phototoxicity and dark toxicity is approximately 50 and evidences a therapeutic window for the application of1 in blue-light photodynamic therapy. Complex1 also enters and efficiently photoinactivates Gram-positive bacteria Enterococcus faecalis and Staphylococcus aureus, documenting its suitability as a blue-light photosensitizer for antimicrobial applications.